A REVIEW OF LITERATURE ON IMPACT OF COVID-19 ON STUDENTS PURSUING HIGHER EDUCATION (International Journal of Food and Nutritional Sciences, 2022)
As a result of the COVID-19 pandemic, different states and municipalities have implemented stay-at-home orders, and numerous ancillary companies have been closed. Also, higher education institutions across the country have shifted from in-person class teaching to remote learning. This article focuses on a review of the literature on the stress experienced by students pursuing higher education due to the influence of COVID-19 isolation. This article will also make recommendations to reduce the COVID effect on student mental health and promote social transformation. The literature review suggests that the stress experienced by students is caused by a variety of factors, including a lack of access to physical resources, disruptions in educational routines such as cancelling classes, hybrid and online learning, and changes in grading policies In addition, the isolation resulting from COVID-19 has created an environment in which many students are struggled to maintain connections with their peers, leading to feelings of loneliness and anxiety. The literature review also found that students are experiencing a heightened sense of financial pressure, both from the economic impacts of COVID-19 and their own personal finances despite these challenges; it is observed that there are several ways in which educational institutions can address student mental health needs during the pandemic. From the review of literature related the study area it is identified that in order to reduce the stress experienced by students, educational institutions should provide more support services, such as mental health counselling and other resources.